The Effectiveness of Cognitive Behavioral Group Counseling in Reducing Fear of Missing Out (FOMO) Among Vocational High School Students - Agus Rizal Agus; Wisnu Kurniawan Wisnu; Amanatul Qudsiyah Ana (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Excessive dependence on social media among adolescents often triggers social anxiety, namely the phenomenon of Fear of Missing Out (FOMO). This condition creates emotional pressure due to the fear of missing out on information or digital trends, which ultimately disrupts students' concentration and psychological well-being. This study aims to evaluate the effectiveness of group counseling interventions using a cognitive behavioral approach in reducing FOMO levels among vocational school students. The research subjects involved a population of 70 students, with a core sample of 20 students divided into experimental and control groups. Additionally, this study involved 31 tenth-grade MP students as test subjects for the instrument to ensure the accuracy of the measurement tool. Data collection used a Likert-scale FOMO questionnaire that had undergone validity and reliability testing with a Cronbach's Alpha value of 0.927. The data analysis technique used was the Independent Samples T-Test parametric statistical test with the assistance of the SPSS program. The results of the study show a significance value (Sig. 2-tailed) of 0.000 (< 0.05), which proves that there is a significant difference in the reduction of FOMO levels between the experimental group that received cognitive restructuring and mindfulness intervention and the control group. The conclusion of this study confirms that Cognitive Behavior-based group counseling services are effective in reducing students' tendency toward FOMO. These results have implications for school counselors to adopt cognitive affective integrative techniques as adaptive guidance service strategies in addressing adolescent mental health issues in the digital age.